Sterilization Of Oil Palm Fruit Using Supercritical Carbon Dioxide As A Green Technology - Lah, Tengku Norsalwani Tuan (2019)
Sterilization is a crucial process for palm oil processing to produce quality palm oil. The purpose of oil palm fruits (OPF) sterilization is to inactivate lipophilic microorganisms, soften the fruit pulp and facilitate the OPF detachment from the stalk. Currently, palm oil industries in Malaysia utilizes the steam sterilization method for OPF processing. This sterilization method requires a huge quantity of water, resulting in generation of large quantities of palm oil mill effluent (POME). Besides, the interaction of OPFs with moisture during steam sterilization is denoting higher free fatty acid (FFA) in extracted oil. Therefore, it urges to implement a waterless sterilization technology to eliminate FFA generation in extracted oil and avoid POME generation. In the present study, Supercritical carbon dioxide (SC-CO2) technology was utilized to sterilize OPF with varying pressure (7.4-50 MPa), temperature (32-80oC) and treatment time (15-60 min). The performance of SC-CO2 sterilization was determined based on the inactivation of lipase producing microorganisms (bacterial and fungi) in OPF and it was compared with steam autoclave sterilization. Results showed that the SC-CO2 inactivated the microorganisms at moderate temperature (≤ 80oC) and pressure (8-10 MPa) within ≤60 min of sterilizing time. The SC-CO2 efficiency of OP-FFB sterilization was determined using a 10 Liter vessel, based on the inactivation of Bacillus spp. and Aspergillus spp. (microbes with highest occurrence) in OP-FFB with varying SC-CO2 pressure (10-30 MPa), temperature (40-80oC) and treatment time (15-90 min).